The Impact of Homelessness and Incarceration on Women's Health. (January 2016) - Ahmed, Rabia A.; Angel, Cybele; Martell, Rebecca; Pyne, Diane; Keenan, Louanne
Female inmates have multiple challenges during incarceration and as they transition into the community including: barriers to accessing health care within correctional facilities, poor transitional preparation preceding release, and inadequate continuity of health care after release. This qualitative study explored the health-seeking experiences and the health and housing needs of female inmates. Four focus groups were conducted in a remand facility in Canada. Women described poor health at entry to the correctional system and viewed incarceration as a means to access health care services. Transition back into the community represented a crossroad that was dependent on the stability of housing status. These findings support gender-sensitive health and housing programs to reduce addictions, recidivism, and poor health among this vulnerable population.